Sedimentary processes in the Discovery Gap (Central–NE Atlantic): An example of a deep marine gateway. (February 2022) - Glazkova, T.; Hernández-Molina, F.J.; Dorokhova, E.; Mena, A.; Roque, C.; Rodríguez-Tovar, F.J.; Krechik, V.; Kuleshova, L.; Llave, E.
Abstract: Paleoceanographic studies of abyssal bottom currents are often complicated by low current speeds and sedimentation rates, resulting in sediment condensation or erosion. However, increased rates of erosion and deposition may occur where bottom current velocities change as they pass through deep marine gaps and gateways. Despite this, the depositional processes in these gateways and their paleoceanographic implications remain poorly understood. Based on new sedimentological, hydrological and geophysical (high resolution seismic and bathymetry) data from Discovery Gap (Azores–Gibraltar Fracture Zone) collected during the 43 rd cruise of the R/V Akademik Nikolaj Strakhov in 2019, the key sedimentary processes occurring in the Late Quaternary have been determined. Two depressions with depths exceeding 5300 m in the centre and south of Discovery Gap have been identified, the latter filled with contouritic deposits. These depressions are separated by a roughly N–S trending central sill at 4860 m and a sediment filled terrace at 4720 m water depth. Elongated NE–SW trending highs and sills, are present in the north and south of the study area. Their importance in controlling the flow of water through Discovery Gap is determined by the presence of erosion at the base of these highs with adjacent sheeted or mounded contourite drifts. Pelagic, hemipelagic, reworked pelagic/hemipelagic and fine-grained contourite sedimentary facies have been identified. The sedimentary facies associations point to remarkable variability in the Antarctic Bottom Water (AABW), linked to glacial–interglacial changes, and its intermittent influence in Discovery Gap during the Quaternary. During glacial intervals (MIS 6, 4 and 2) and at their terminations there was enhanced bottom current activity coeval with higher terrigenous content, and increased carbonate dissolution. The results of this study improve our understanding of sedimentary processes in abyssal environments and highlight the value of the sedimentary record in deep marine gateways for interpreting the interaction of bottom water with abyssal morphology. Future work in other modern deep gaps is essential to shed more light on how deep gaps form and to fully reconstruct deep-water paleocirculation within oceanic basins. Highlights: Northwards-flowing bottom currents affect the deposition and reworking of sediment in the gap. Sediments may come from the surface waters, Madeira abyssal plain or surrounding topography. Bottom current intensity relates to climatic shifts in the Quaternary.